2017
DOI: 10.1186/s12936-017-1789-9
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic and sub-microscopic malaria infection in Kayah State, eastern Myanmar

Abstract: BackgroundMyanmar has the heaviest burden of malaria in the Greater Mekong Sub-region. Asymptomatic Plasmodium spp. infections are common in this region and may represent an important reservoir of transmission that must be targeted for malaria elimination.MethodsA mass blood survey was conducted among 485 individuals from six villages in Kayah State, an area of endemic but low transmission malaria in eastern Myanmar. Malaria infection was screened by rapid diagnostic test (RDT), light microscopy and real-time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
47
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 30 publications
6
47
4
Order By: Relevance
“…However, this figure is lower than previous studies in Kenya 12.6% (28) and Tanzania 8% (29). Lower findings than the current study were reported in Malo, Southwest Ethiopia with no case (17), Myanmar 1.4% (30), and Haiti with 2.8% (24). This difference might be due to parasitemia level, variation in transmission setting, and skills of laboratory personnel.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…However, this figure is lower than previous studies in Kenya 12.6% (28) and Tanzania 8% (29). Lower findings than the current study were reported in Malo, Southwest Ethiopia with no case (17), Myanmar 1.4% (30), and Haiti with 2.8% (24). This difference might be due to parasitemia level, variation in transmission setting, and skills of laboratory personnel.…”
Section: Discussioncontrasting
confidence: 94%
“…The polymerase chain reaction (PCR) detected and identified 12% of asymptomatic Plasmodium spp infection. This was higher than previous studies in Ethiopia; with 8.12% (17,18), Myanmar with 2.3% (30), Zambia with 8% (31). However, it was lower than findings in Southeast Asia with 20% 22 Moreover, the present study revealed that PCR invariably detected higher proportion of asymptomatic infection with about 2.7 and 2.3 folds higher than RDT and microscopy, respectively.…”
Section: Discussioncontrasting
confidence: 71%
“…The prevalence of asymptomatic Plasmodium infection was higher using microscopy than RDT which disagrees with a report from the rural surroundings of Arbaminch Town, South Ethiopia [6]. However, the finding was consistent with the study findings reported from Tanzania and Myanmar [16,17]. There was statistically significant association between ITN usage habit and plasmodium infection in pregnant women.…”
Section: Discussioncontrasting
confidence: 55%
“…Depending on the RDT used and study setting and design, RDT may 26,27 or may not 28,29 perform better than microscopy in detecting SMI. Such infections, if undetectable by the current generation of RDTs, may compromise the current focus on malaria elimination in PNG.…”
Section: Discussionmentioning
confidence: 99%